High repetition rate laser-induced breakdown spectroscopy using acousto-optically gated detection - Pořízka, Pavel; Klessen, Benjamin; Kaiser, Jozef; Gornushkin, Igor; Panne, Ulrich; Riedel, Jens (The Review of scientific instruments, 2014)
This contribution introduces a new type of setup for fast sample analysis using laser-induced breakdown spectroscopy (LIBS). The novel design combines a high repetition rate laser (up to 50 kHz) as excitation source and an acousto-optical modulator (AOM) as a fast switch for temporally gating the detection of the emitted light. The plasma radiation is led through the active medium of the AOM where it is diffracted on the transient ultrasonic Bragg grid. The diffracted radiation is detected by a compact Czerny-Turner spectrometer equipped with a CCD line detector. Utilizing the new combination of high repetition rate lasers and AOM gated detection, rapid measurements with total integration times of only 10 ms resulted in a limit of detection (LOD) of 0.13 wt.% for magnesium in aluminum alloys. This short integration time corresponds to 100 analyses/s. Temporal gating of LIP radiation results in improved LODs and consecutively higher sensitivity of the LIBS setup. Therefore, an AOM could be beneficially utilized to temporally detect plasmas induced by high repetition rate lasers. The AOM in combination with miniaturized Czerny-Turner spectrometers equipped with CCD line detectors and small footprint diode pumped solid state lasers results in temporally gateable compact LIBS setups.